KOMUNITAS MAKROZOOBENTOS DI SUNGAI BATANG LUBUH KECAMATAN RAMBAH KABUPATEN ROKAN HULU - Aditya Apmayasari; Radith Mahatma; Khairijon ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Batang Lubuh river has significant value to communities living close to the river. Generally, the people take some advantages from the river, such as for household activities (bath, washing and dumping the waste) and fishery. In addition, the river shed is such a beneficial for agriculture and mining. The use of macrozoobenthos as an indicator to identify the change of water quality was reported by some authors, but the information from Riau Province is scarce. The purpose or this research is to know the community structure or Macrozoobenthos at Batang Lubuh river, sub – district Rambah, Rokan Hulu Regency. Sampling was conducted using Eckman Grab 20 cm x 11 cm at 5 station along Batang Lubuh river of sub district Rambah, Rokan Hulu Regency. During this research we found two species of macrozoobenthos, Brotia costula family Thiaridae and Pila scutata family Ampullaridae. The abundance of macrozobenthos in study area was 408 ind/m2. Besides, we also found that Brotia costula as the dominant species. Regression analysis revealed that the correlation between physical and chemical factors such as temperature, brightness, depth, flow velocity, COD and phosphate on macrozoobentos was negative. In addition, DO and nitrate have a positive correlation to macrozoobenthos, while pH and turbidity have no correlation to macrozoobenthos.